Estimating energy consumption and charging duration of electric vehicle in multigraph. (July 2023) - Karimpour, Asal; Setak, Mostafa; Hemmati, Ahmad
Abstract: The two main features of electric vehicles are their ability to recuperate energy and their spent time in charging stations, including the waiting time in the queue and the battery charge duration. In this paper, we focus on estimating energy consumption and charging duration in an Electric Vehicles Routing Problem on a multigraph that incorporates a queuing model at charging stations. We develop a mathematical model and propose an Adaptive heuristic to solve the problem. The heuristic approach is compared with an exact solution on small-size instances and a Tabu Search algorithm. Computational results are also provided in larger and more realistic instances. Furthermore, we find that increasing the waiting time in the queue may lead to higher costs whereas the existence of alternative paths may reduce expenses. Finally, we conduct a sensitivity analysis to illustrate the impression of the model parameters on the solution. Highlights: This article focuses on Electric vehicles and energy issues. Energy consumption and battery charging are investigated in the route planning. Electric vehicle Routing is applied to the transport system with alternative paths. The queuing model and charging duration at battery charging stations are considered. An adaptive heuristic is provided to solve Electric Vehicle Routing on a multigraph.